THE DARK SIDE OF USING SOCIAL MEDIA : IMPACT UPON INTERNET USERS - Abdul Rani, Nur Shazana; Nazira Ibrahim, Noor Afzaliza; Sah Allam, Siti Nur Shahidah; Jamri, Mohamad Hafifi; Ridzuan, Abdul Rauf; Syed Mostapa, Syed Muhammad Fauzi Syed Mostapa (I-iECONS e-proceedings, 2023)
One of the most popular forms of interactive computing is social media, which involves technology that allows peopleto communicate and exchange information. Being able to communicate easily and getting to know more about aparticular person has become easier nowadays. However, this can also be taken to another level where stalking becomes easier to be done by or for users. In Malaysia, the highest percentage of social media users are teenagers from 15 to 19 years old. This research will focus on how teenagers are more prone to develop cyberstalking tendencies and if they are aware of the line of privacy on social media. The method that the researcher used to conduct this research was in-depth interview to collect data. Twenty social media users were selected to be interviewed by the researcher and the respondents were interviewed with the questions that have been prepared. All the data and information was transcribed (verbatim) and thematic data analysis was used to sort out all the data and information. In particular, the findings highlight the truth behind the development of cyberstalking among teenagers due to the influence of social media.